2005
DOI: 10.1557/jmr.2005.0282
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Epitaxial SrTiO3/Pt/Ti/ Sapphire Heterostructures

Abstract: The microstructure and orientation relationships of epitaxial (111)-oriented SrTiO3 thin films grown by radio frequency magnetron sputtering on epitaxial (111)-oriented Pt/Ti electrodes on sapphire were investigated using x-ray diffraction, conventional and scanning transmission electron microscopy. We show that the epitaxial growth of (111)-oriented SrTiO3 films was promoted by thin Ti adhesion layers underneath the Pt electrode. The SrTiO3 films nucleated with two twin-related orientation variants, rotated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
4
16
1
Order By: Relevance
“…Some (100) oriented grains could also be detected in XRD. In contrast, the SrTiO 3 films grown on the electron beam evaporated Pt with Ti adhesion layers contained mostly (111) oriented grains, as was confirmed by plan-view TEM studies that will be reported elsewhere [16]. The (111) peaks of SrTiO 3 in the XRD spectra ( Fig.…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 81%
See 1 more Smart Citation
“…Some (100) oriented grains could also be detected in XRD. In contrast, the SrTiO 3 films grown on the electron beam evaporated Pt with Ti adhesion layers contained mostly (111) oriented grains, as was confirmed by plan-view TEM studies that will be reported elsewhere [16]. The (111) peaks of SrTiO 3 in the XRD spectra ( Fig.…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 81%
“…Substrates for the electron beam evaporated Pt electrodes were covered with ~ 3 nm thick e-beam Ti adhesion layers, which significantly affected the texture of the SrTiO 3 films subsequently grown onto them, as described below. As reported elsewhere [14][15][16] . The epitaxial Pt films showed rotational twinning [14,15,17].…”
Section: Methodssupporting
confidence: 54%
“…Despite their technological importance, relatively few studies have succeeded in obtaining an atomic level understanding of these interfaces. Pt/SrTiO 3 thin film heterostructures are an ideal model system [10][11][12][13]. SrTiO 3 is an incipient ferroelectric with the cubic perovskite structure and it has a small lattice mismatch with Pt (~ 0.4 % at room temperature).…”
mentioning
confidence: 99%
“…SrTiO 3 is an incipient ferroelectric with the cubic perovskite structure and it has a small lattice mismatch with Pt (~ 0.4 % at room temperature). We have recently shown that (111) SrTiO 3 thin films can be grown epitaxially on (111) oriented epitaxial Pt electrodes on (0001) sapphire if a thin (~ 3 nm) Ti layer was deposited under the Pt electrode [13]. If no Ti layer was present, the SrTiO 3 thin films were predominantly (110) oriented, although they also showed an epitaxial relationship with the (111) Pt electrode [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation